The Polish Wage Curve: Micro Panel Data Analysis Based on the Polish Labor Force Survey - Badi H. Baltagi; Bartlomiej Rokicki (Institute for the Study of Labor (IZA), 2013)
This paper analyzes the Polish wage curve using individual data from the Polish Labor Force Survey (LFS) at the 16 NUTS2 regions over the period 1999 - 2010. This survey does not gather information on wages of self-employed or paid family workers. After excluding the unemployed, inactive and missing observations, we are left with over 102,924 observations. We find evidence in favor of the Polish wage curve with an unemployment elasticity of -0.06. We also find that males in Poland are significantly more responsive to local unemployment rates (-0.08) than their female counterparts (-0.04). Moreover, if the lagged unemployment rate is used as an instrument for current unemployment rate, we find that the unemployment elasticity increases substantially for less experienced and temporary workers.
Keywords: C26; J30; J60; 330; wage curve; fixed effects; regional labor markets